Policy Transfer In Critical Perspective: The Case Of Malaysia My Second Home Programme - Rahman, Nurulhasanah Abdul (2022)
Malaysia My Second Home Programme (MM2H) was established in 2002 as a government initiative programme to promote Malaysia as a retirement hub for financially qualified foreigners. Although the programme is in high demand to boost Malaysia’s economy and tourism industry, the actual MM2H programme achievement is hampered by many policy problems. Therefore, it is crucial to investigate the root of the problem by analysing the programme using the policy transfer approach. To address this need, the focus of the study aimed to explore the exact process of policy transfer in the MM2H programme and propose recommendations for policy improvement. Elite interviews using semi-structured questions were conducted among 13 policy actors consisting of public officers and academicians. All interview data were triangulated with the policy documents and finally mapped into the Policy Transfer Framework. One of the main findings revealed that the process of policy transfer in the MM2H programme was first initiated in 1998 as a response to the unprecedented Asian financial crisis in 1997. Additionally, the MM2H programme was confirmed as an output of the internal policy transfer practice. In particular, it was a transferred policy from another era in 1987 through the Silver Hair Programme by drawing negative lessons and addressing past policy potentials.